2016
DOI: 10.1093/ejcts/ezw103
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of left ventricular surgical remodelling after the STICH trial

Abstract: Our findings show that patients, who are candidates for LVSR, have mostly akinetic areas and CIMR requiring surgical correction and are severely symptomatic. Severe LVDD is common and, along with emergency status, is the most important risk factor for early and late outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Moreover, in this study fewer patients underwent CABG (71.5%) than in the RESTORE study (95%) and the STICH trial (100%). Overall, the 5-year survival in this study (72.1%) was comparable to that of the RESTORE study (68.6%), the STICH trial, and other studies ( 5 , 23 , 31 ).…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, in this study fewer patients underwent CABG (71.5%) than in the RESTORE study (95%) and the STICH trial (100%). Overall, the 5-year survival in this study (72.1%) was comparable to that of the RESTORE study (68.6%), the STICH trial, and other studies ( 5 , 23 , 31 ).…”
Section: Discussionsupporting
confidence: 76%
“…Although ventricle reshaping has been viewed as controversial, with a landmark surgical study showing no significant increase in survival or functional outputs (40), subsequent reports have argued this was the result of surgical reshaping that focused on volume rather than shape (39,41).…”
Section: Discussionmentioning
confidence: 99%
“…After the outcome of the STICH Trial’s hypothesis 2, research on the treatment of SVR was intensified, and authors like Isomura [23] demonstrated that this procedure is more effective when 33% of ventricular reduction is obtained and LVESVI < 90 ml/m 2 , as well as there is no long-term benefit when SVR induces a left ventricular volume reduction < 15% and leaves residual LVESVI > 90 ml/m 2 . Calafiore [24] , in a group of patients with ischemic mitral insufficiency in 90.3% of them and NYHA III-IV in 77.9%, with mean EF of 26%, and akinetic areas at the site of ventricular scar in 86.7%, demonstrated no deaths from any cause and NYHA III-IV in 61%.…”
Section: Discussionmentioning
confidence: 99%